CINNARIZINE LIQUID SOLID COMPACTS: PREPARATION EVALUATION - Sisinthy, Sreenivas Patro; Selladurai, Shubbaneswarei (International Journal of Applied Pharmaceutics, 2019)
Objective: The objective of this research was to formulate cinnarizine tablets using the liquid-solid compact technique to enhance its solubility and dissolution rate. Methods: Cinnarizine liquid-solid compacts were formulated using propylene glycol as the non-volatile solvent, Neusilin US2 as the carrier material, Aerosil 200 as the coating material and croscarmellose sodium as the disintegrant. The interaction between drug and excipients were characterized by Fourier-transform infrared spectroscopy (FTIR) and differential scanning calorimetry (DSC) studies. Different batches of liquid, solid compacts were prepared by using varying carrier-coating excipient ratio and different concentration of liquid medication. Flow parameters such as bulk density, tapped density, Carr's Index, Hausner's Ratio as well as an angle of repose were used to test the flowability of the powder blend. The liquid-solid compacts were produced by direct compression method and were evaluated for tests such as weight variation, drug content, hardness, thickness, friability, wetting time, disintegration time as well as the in vitro dissolution studies. Results: The results of the preformulation studies of liquisolid compacts showed acceptable flow properties. The results of FTIR and DSC studies showed that there is no drug-excipient interactions. The different R values and concentrations were found to have a marked effect on the dissolution profile. Formulations with higher carrier: coating ratio (R-value) and lower drug concentrations displayed a better dissolution profile. The percentage of drug release of F3 with an R-value of 20 and a drug concentration of 10% was found to be 88.11% when compared to the conventional marketed tablet which released only 44.07% at the end of 2 h. Conclusion: From this research, it is inferred that liquid-solid technique is a promising and effective approach that can be used to enhance the dissolution rate of cinnarizine.